Efficacy of Flipped Classroom and Didactic Lecture Approaches in Undergraduate Respiratory Medicine Education - Ramesh Pandey; Satyendra Mishra; Manoj Sahu; Talha Saad; Nitu Mishra; Saumya Saxena (Journal of Pharmacy and Bioallied Sciences)
Background: This study used a mixed-methods design, analyzing quantitative pre- and post-assessment scores alongside qualitative student feedback. Undergraduate students in Respiratory Medicine were randomly assigned to either the Flipped Classroom or Didactic Lecture groups. Method: The study compares the effectiveness and perceived impact of the Flipped Classroom versus Didactic Lecture approaches in Undergraduate Respiratory Medicine Education. Results: The Flipped Classroom group showed significantly higher post-assessment scores and positive feedback, highlighting increased engagement, collaborative learning, and self-directed study. Conclusion: The study supports the effectiveness of the Flipped Classroom over traditional lectures, emphasizing active student involvement and personalized learning in Respiratory Medicine education.